Substance use in children and adolescents and forensic toxicological analysis - Aslan, Rukiye; Aktaş, Alev; Annette Akgür, Serap (Journal of Dependence, 2023)
Alcohol and substance use is one of the important public health and safety problems that threaten society. Our country has a high young population, children and adolescents constitute an important part of the society and adolescents are in the most important risk group in terms of Alcohol and Substance Use Disorders (AMD). New varieties are added to the substances used) over the years and this poses a risk for substance use, especially at an early age. However, many risk factors and protective factors for substance use change over time. In terms of public safety and public health, especially in the case of control and/or use of these illegal substances, substance tests for diagnosis-monitoring are of great importance as concrete data, as well as serious evidence. A fair and healthy service will be provided to our children by carrying out the medical, social or legal procedures for the determination of the substances used with a holistic and systematic approach. In this review, a general profile of the substance use problem in children and adolescents in our country and in the world is presented, the risk of substance use and protective factors, the fight against substance use in children and adolescents, forensic toxicological analysis and biological materials are discussed.
Keywords: Children and adolescent; alcohol and substance use disorders; forensic toxicological analysis